A Comparative Study of Positive Criminal Law and Islamic Criminal Law on Child Protection - Ida Lestiawati; Nurdin Nurdin; Marzuki Marzuki (State Islamic University Datokarama Palu, 2026)
This study examines legal protection against the commercial sexual exploitation of children through a comparative analysis of Indonesian criminal law and Islamic criminal law. Using a normative legal research method with a prescriptive approach, the study analyzes legal doctrines, statutory regulations, Islamic legal principles, and relevant literature. The findings reveal that commercial sexual exploitation of children remains influenced by poverty, socio-cultural conditions, political factors, social stigma, and weaknesses in law enforcement. Indonesian criminal law provides protection through a mixed sentencing system emphasizing punishment, prevention, and victim protection, while Islamic criminal law offers a comprehensive framework based on maqashid al-shari'ah and ta'zir sanctions. The comparative analysis demonstrates that integrating the legal certainty of positive law with the moral and preventive values of Islamic law can strengthen child protection and enhance efforts to prevent and combat commercial sexual exploitation of children. The study proposes a reconstructed legal protection model that is more comprehensive, victim-oriented, and responsive to contemporary challenges.